A model of the Islamic sovereign wealth fund. Issue 1 (30th May 2019) - Bahoo, Salman; Hassan, M. Kabir; Paltrinieri, Andrea; Khan, Ashraf
Abstract : Purpose: The purpose of this paper is to propose a model of the Islamic sovereign wealth funds (ISWFs) based on Islamic finance principles to modify the precarious image of SWFs from Muslim countries. The Shariah laws are the cardinal direction for this study. Design/methodology/approach: The authors applied a qualitative research technique that consists of three approaches: exploratory case study approach to critically examine and rank the existing status of SWFs; descriptive analysis; and content analysis to present a model of ISWFs in comparison of conventional SWFs. Findings: The authors propose a model of the "Islamic Sovereign Wealth Funds" based on four key pillars: the major Shariah principles; the Islamic corporate governance framework; the Islamic transparency and disclosure framework; and the Islamic corporate social responsibility framework. Furthermore, the authors argue that the potential effect of the ISWFs on Islamic finance and economy will be positive. Research limitations/implications: The model is an initial work and idea to convert SWFs from Muslim countries into ISWFs, which required an in-depth policy review by governments. Practical implications: The findings of the paper are useful for policymakers and governments of the Muslim countries to overcome the issues and criticism on SWFs by converting them in ISWFs. Originality/value: This paper contributes to the literature related to Islamic finance and sovereign wealth fund by presenting a first model of ISWFs for Muslim countries.